1998
DOI: 10.1182/blood.v91.1.75.75_75_88
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Ability of Bone Marrow Stromal Cells to Support B-Lymphopoiesis With Age

Abstract: B-lymphopoiesis decreases with age. We studied how aging affects bone marrow stromal cells, because they provide the growth factors and cell contacts required for B-lymphopoiesis. No differences were noted in the cell-surface phenotype of young and old primary-cultured stromal cells. Fluorescence-activated cell sorter-purified stromal cells from old mice were deficient in the ability to support the proliferation of interleukin-7 (IL-7)–specific B-lymphoid cell lines. The kinetics of this response indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Although total B cell counts remain relatively stable in the adult population, a reduced output of naive B cells from the bone marrow (BM) has been reported in mouse and human studies (226)(227)(228)(229). Decreased production of IL-7 by stromal cells in the BM, reduces the size of the B cell progenitor population and affects B lymphopoiesis (230)(231)(232). The function of hematopoietic stem cells (HSCs) declines with age and shifts toward the generation of non-lymphoid cells, therefore reducing the source of B cell progenitors.…”
Section: B Lymphocytesmentioning
confidence: 99%
“…Although total B cell counts remain relatively stable in the adult population, a reduced output of naive B cells from the bone marrow (BM) has been reported in mouse and human studies (226)(227)(228)(229). Decreased production of IL-7 by stromal cells in the BM, reduces the size of the B cell progenitor population and affects B lymphopoiesis (230)(231)(232). The function of hematopoietic stem cells (HSCs) declines with age and shifts toward the generation of non-lymphoid cells, therefore reducing the source of B cell progenitors.…”
Section: B Lymphocytesmentioning
confidence: 99%
“…The development of B cells is critically dependent upon the stromal environment within the BM [34], and although maturation of B cells resides within a different compartment, which is associated with HSC differentiation, given the agerelated changes within the BM niche [15], the defects of B cell function in the aged could nevertheless be attributed, in part, to the aged microenvironment. Previous studies have shown that primary culture of stromal cells from old and not young fail to support B cell development, due possibly to a defect in the secretion of interleukin (IL)-7, a key cytokine for B cell maturation, from ageing stromal cells [35]. Adoptive transfer experiments suggest that the aged BM stroma may reduce the recombinase activity in B cell progenitors which leads to the inability to undergo gene rearrangement, resulting in a decrease in B cell differentiation [36].…”
Section: The Aged Bone Marrow Nichementioning
confidence: 99%
“…In addition to an aging-associated decrease in self renewal of HSCs in the bone marrow, a reduction in the differentiation of progenitor B cells, precursor B cells and immature B cells has for instance been correlated to the presence of aged bone marrow stroma in aged mouse models ( 73 , 130 ). This impaired differentiation can be partially attributed to a reduced capacity of the murine progenitor B cells to respond to stromal derived IL-7 on which they depend for their survival ( 131 , 132 ). Similar to T cells, a reduction in B cell precursors in lymphoid organs could conceivably impact the diversity of the BCR repertoire.…”
Section: Aged Adaptive Immunity In Atherosclerosismentioning
confidence: 99%